Emergency bailout surgery saves lives in high‐risk patients with complications after TAVR. Issue 11 (19th September 2022) - Combaret, Nicolas; d'Ostrevy, Nicolas; Innorta, Andrea; Motreff, Pascal; Eschalier, Romain; Clerfond, Guillaume; Pereira, Bruno; Souteyrand, Géraud
Abstract: Introduction: With the expansion of the indication for transcatheter aortic valve implantation (TAVR), the value of access to on‐site emergency heart surgery at performing centers needs to be assessed. Aims: To evaluate postoperative mortality after surgical rescue post‐TAVR, in a population at high surgical risk. Methods: Retrospective analysis of a cohort of patients included in the France‐TAVI registry who had undergone TAVR with the latest generation valves between January 2017 and February 2020. Results: Among the 968 patients undergoing TAVR, 6 patients (0.62%) were identified as candidates for surgery: 3 in the peri‐operative context and 3 during hospitalization. Four subjects were managed in a salvage situation, two due to tamponade, one due to aortic dissection, and one due to aortic annulus rupture. One patient died of a delayed aortic annulus rupture and one patient presented a right coronary occlusion which was medically treated. All patients who underwent emergency surgery were discharged alive from the hospital. Conclusions: In TAVR patients initially contraindicated for surgery, emergency bailout surgery could be performed successfully with all patients discharged alive. Access to on‐site heart surgery represents a life‐saving resource for TAVR centers.